Establishment and Verification of a Thermal Calculation Model Considering Internal Heat Transfer of Accumulated Water in Permafrost Regions - Peng, Erxing; Hu, Xiaoying; Sheng, Yu; Zhou, Fansheng; Wu, Jichun; Cao, Wei (Frontiers in Earth Science, 2021)
Water accumulation in permafrost regions causes a heavy thermal impact on the frozen layer, thereby leading to its degeneration. First, based on the real heat transfer process, this study proposes relevant hypotheses and governing equations for heat calculation models involving completely melted water, ice-bearing water, water-soil interface, and soil under water. The models consider water surface as a thermal boundary on account of the natural buoyancy convection mechanism in water and the phase transition process. Second, this study verifies the accuracy of the calculation models as regards the measured water and permafrost temperatures. The four seasonal vertical temperature changes in the water according to this model are found to be consistent with the actual temperature-change trend, and the permafrost temperature under water is also consistent with the actual temperature field. This study thus provides theoretical support for the thermal impact analysis of water in permafrost regions.